Downward Trend in Maternal Mortality Ratio in Khorasan Razavi Province, Iran - Morteza Talebi Doluee; Hoda Zabihi; Behrang Rezvani; Bahram Zarmehri; Mona Najaf Najafi (Mashhad University of Medical Sciences, 2018)
Background & aim: Maternal mortality is defined as the death during pregnancy or up to 42 days postpartum. This study sought to determine the trend of maternal mortality ratio (MMR) and its associated factors in Khorasan Razavi province, Iran. Methods: This retrospective cross-sectional study was conducted in Khorasan Razavi Province, North East of Iran, during 2010 to 2014. Data was collected from the reports of Maternal Mortality Committee of Mashhad University of Medical Sciences, Mashhad, Iran. The MMR was calculated for each period, and its trend was estimated. Chi-square test was used to find the relationship between mode of delivery and direct or indirect causes of maternal death. Results: According to the results, 94 maternal deaths occurred during 2010 to 2014. The total MMR was 17.68 (95%CI: 13.59-21.77) per 100,000 live births. The mean maternal age was 30.7±6.1 years old. Most of the deaths (75.6%) occurred during postpartum period, from which 81% happened following a high-risk pregnancy. In addition, 50% of the mothers had proper numbers of visits during pregnancy. The most direct and indirect causes of maternal death were maternal hemorrhage (24.5%) and cardiovascular diseases (12.8%), respectively. The relative risk of maternal mortality associated with cesarean section was 1.3 in comparison to normal vaginal delivery. Conclusion: The estimation of MMR is essential for decision-making and resource allocation. To reach this goal, a good registration system is needed to register all deaths and their exact causes.